Long noncoding RNA HOTTIP promotes the metastatic potential of ovarian cancer through the regulation of the miR‐615‐3p/SMARCE1 pathway - Hong Wu; Hong‐Yan Wei; Qian‐Qian Chen (Kaohsiung Journal of Medical Sciences, 2020)
Abstract Upregulation of lncRNA HOXA transcript at the distal tip (HOTTIP) plays important roles in cancer progression. Nevertheless, its functions in the growth and metastasis of ovarian carcinoma are unknown. In this study, we demonstrated overexpression of HOTTIP in ovarian cancer cell lines and clinical tissues. Further, we showed that higher level of HOTTIP was associated with poor survival of ovarian cancer patients. Notably, HOTTIP silencing restrained proliferation, migration, and invasiveness of ovarian carcinoma cells. On the other hand, upregulation of HOTTIP remarkably exacerbated the aggressive traits of ovarian carcinoma cells. In addition, HOTTIP served as a sponge of miR‐615‐3p to upregulate SMARCE1 level. Further, upregulation of miR‐615‐3p or downregulation of SMARCE1 reversed the carcinogenic impacts of HOTTIP in ovarian cancer. HOTTIP and miR‐615‐3p expression levels in ovarian cancer cells were negatively correlated, whereas HOTTIP and SMARCE1 expression levels were positively correlated. In nude mice, downregulation of HOTTIP reduced cell growth in vivo. In summary, lncRNA HOTTIP promotes the growth and metastatic phenotypes of ovarian cancer via regulating miR‐615‐3p/SMARCE1 pathway.